Program Kemitraan Masyarakat Home Industry Kacang Sangrai Desa Cisoka Kabupaten Tangerang - Chandra Dwiaji, Yudhi; Sulistyowati, Niken (Indonesia Berdaya, 2021)
The purpose of this service is to provide training and knowledge to partners in using appropriate technology so that the productivity and efficiency of the Cisoka’s roasted bean craftsmen's activities increases. The method used in this activity is participatory and collaborative methods where partners participate in activities such as socialization and training, operation and maintenance of roasting machines and packaging sealer machines. Abstrak: Tujuan pelaksanaan pengabdian ini adalah untuk memberikan pelatihan dan pengetahuan kepada mitra dalam penggunaan TTG agar produktivitas dan efisiensi kegiatan pengrajin kacang sangrai Cisoka meningkat. Metode yang digunakan dalam kegiatan ini adalah metode parsipatori dan kolaboratif dimana mitra ikut berpartisipasi dalam kegiatan seperti sosialisasi dan pelatihan, pengoperasian dan pemeliharaan mesin sangrai dan mesin sealer kemasan.